Molecular Cloning and Functional Characterization of a Novel Isoflavone 3′-O-methyltransferase from Pueraria lobata - Li, Jia; Li, Changfu; Gou, Junbo; Zhang, Yansheng (Frontiers in Plant Science, 2016)
Pueraria lobata roots accumulate 3′-, 4′- and 7-O-methylated isoflavones and many of these methylated compounds exhibit various pharmacological activities. Either the 4′- or 7-O-methylation activity has been investigated at molecular levels in several legume species. However, the gene encoding the isoflavone 3′-O-methyltransferase has not yet been isolated from any plant species. In this study, we reported the first cDNA encoding the isoflavone 3′-O-methyltransferase from P. lobata (designated PlOMT4). Heterologous expressions in yeast and Escherichia coli cells showed that the gene product exhibits an enzyme activity to methylate the 3′-hydroxy group of the isoflavone substrate. The transcript abundance of PlOMT4 matches well with its enzymatic product in different organs of P. lobata and in the plant roots in response to methyl jasmonate elicitation. Integration of the biochemical with metabolic and transcript data supported the proposed function of PlOMT4. The identification of PlOMT4 would not only help to understand the isoflavonoid metabolism in P. lobata but also potentially provide an enzyme catalyst for methylating existing drug candidates to improve their hydrophobicity.